2020
DOI: 10.3390/nu12020325
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of a 6-Month High Dose Omega-3 and Omega-6 Polyunsaturated Fatty Acids and Antioxidant Vitamins Supplementation on Cognitive Function and Functional Capacity in Older Adults with Mild Cognitive Impairment

Abstract: The aim of the present study was to examine the effects of a high-dose omega-3 and omega-6 fatty acids supplementation, in combination with antioxidant vitamins, on cognitive function and functional capacity of older adults with mild cognitive impairment (MCI), over a 6-month period in a randomized, double-blind, placebo-controlled trial. Forty-six older adults with MCI (age: 78.8 ± 7.3 years) were randomized 1:1 to receive either a 20 mL dose of a formula containing a mixture of omega-3 (810 mg Eicosapentaeno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
28
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(34 citation statements)
references
References 78 publications
4
28
0
2
Order By: Relevance
“…When intervention trials on parameters of cognition published up to 2015 were broken down according to dose of DHA used, it became apparent that trials using more than 600 mg DHA per day had positive results in terms of aspects of memory, executive function, or aspects of learning, while those using lower doses largely had neutral results [ 12 ]. However, more recently, both neutral and positive results were published with doses >600 mg DHA per day [ 119 , 120 , 121 , 122 , 123 , 124 , 125 ]. One trial found the improvement in executive function and verbal fluency to correlate with the increase of EPA in red cells, as well as improvements in pertinent brain structures [ 126 ].…”
Section: Brain Health In Adulthood–cognition and Dementiamentioning
confidence: 99%
“…When intervention trials on parameters of cognition published up to 2015 were broken down according to dose of DHA used, it became apparent that trials using more than 600 mg DHA per day had positive results in terms of aspects of memory, executive function, or aspects of learning, while those using lower doses largely had neutral results [ 12 ]. However, more recently, both neutral and positive results were published with doses >600 mg DHA per day [ 119 , 120 , 121 , 122 , 123 , 124 , 125 ]. One trial found the improvement in executive function and verbal fluency to correlate with the increase of EPA in red cells, as well as improvements in pertinent brain structures [ 126 ].…”
Section: Brain Health In Adulthood–cognition and Dementiamentioning
confidence: 99%
“…For example, the connection between atherosclerosis and dementia has been well-established [43], and a meta-analysis of randomized controlled trials showed that omega-3 fatty acids significantly slowed the progression of atherosclerosis [44], suggesting that omega-3 fatty acids could potentially prevent cognitive decline through improvements in vascular health. One recent trial showed that six months of supplementation with omega-3 and omega-6 fatty acids in combination with antioxidant vitamins reduced both cognitive and functional decline in adults with mild cognitive impairment [5]. Although mechanistic pathways were outside the scope of the secondary analysis, the authors suggested that omega fatty acids may have acted partially through improvements in endothelial function [5].…”
Section: Discussionmentioning
confidence: 99%
“…One recent trial showed that six months of supplementation with omega-3 and omega-6 fatty acids in combination with antioxidant vitamins reduced both cognitive and functional decline in adults with mild cognitive impairment [5]. Although mechanistic pathways were outside the scope of the secondary analysis, the authors suggested that omega fatty acids may have acted partially through improvements in endothelial function [5]. Indeed, the observed improvement in functional capacity, including an increase in distance walked on the 6-min walk test, coupled with enhanced cognitive function [5] points to a systemic effect of supplementation, which could be explained by whole-body improvement in vascular function that includes higher CBF.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations